Representation of the Imagination of Western and Eastern Orientalism in the Novel Sang Raja by Iksaka Banu: A Postcolonial Study - Arba Al Fitriatus Sofyan; Andaru Ratnasari (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe and explain the Orientalist imagination in Iksaka Banu’s novel Sang Raja using Edward W. Said’s framework, namely: (1) the Oriental imagination as a simple and inferior native, (2) the Western imagination as a superior and legitimate subject, and (3) the ambivalent imagination in the power relations between the West and the East. The study was conducted on the novel *Sang Raja* by Iksaka Banu. The research source was the novel *Sang Raja*, while the research data consisted of narrative excerpts, dialogues, and events containing representations of Western and Eastern Orientalism. The research instrument was the researcher themselves, aided by a corpus of data. Data analysis was conducted using a qualitative descriptive method with content analysis techniques. The results of the study indicate the presence of stereotypes of Eastern inferiority, constructions of Western superiority, and ambivalence in power relations. These findings confirm that Orientalism is not merely an imaginative representation but also functions as ideological legitimization of colonial domination.